Digital Simulations in Science Learning: A Student Perspective on Interactive, Engagement, Conceptual Understanding, and Learning Satisfaction - Wahidin, Wahidin; Gutierrez, Grace; Osman, Kamisah; Akkapin, Supaphorn; Tan, Michael Lip Thye (International Journal of Educational Qualitative Quantitative Research, 2025)
Digital-based learning media offers a solution to overcome the limitations of laboratory practice and creates opportunities for more interactive, visual, and contextual learning experiences. Digital simulations in science education represent an innovative form of learning media in the era of technological transformation. However, students’ perceptions as users of learning media are closely linked to key indicators used to evaluate its effectiveness. This study aims to analyze students' perceptions of using digital simulation media in relation to learning interactivity, engagement, conceptual understanding, and satisfaction within the context of science education. A quantitative approach was employed using a survey method. Data were collected through online questionnaires from 400 high school and university students in Indonesia, Malaysia, Thailand, Singapore, and the United States of America. The data were then analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS software. The results indicated that all proposed hypotheses were statistically supported. Students’ perceptions of digital simulations had a significant positive effect on perceived learning interactivity (H1), learning engagement (H2), conceptual understanding (H3), and learning satisfaction (H4). Positive student perceptions of digital learning media were strongly associated with improvements in the quality of learning interactivity, conceptual understanding, and overall satisfaction. This study makes an important empirical contribution to the development of digital learning media based on student perceptions and provides a foundation for selecting digital-based learning tools that are more responsive, engaging, and effective in the future.